Economic Value of Bamboo Leaf on Nutrition Intake, Productivity, and Growth Performance on Boer Goat - Moh Zali (Jurnal Penelitian Pendidikan IPA, 2024)
This study investigated the effects of bamboo leaf supplementation on nutrition intake, productivity, and growth performance in Boer goats (Capra aegagrus hircus). A randomized complete block design was employed, with four treatment groups: Control (no bamboo leaf supplementation) and three experimental groups receiving Low Dose (50g/day/goat), Medium Dose (100g/day/goat), and High Dose (150g/day/goat) of bamboo leaves. Each treatment group comprised three repetitions. Thirty-six healthy Boer goats of similar age and weight were selected and housed individually with ad libitum access to water and a basal diet. Bamboo leaf supplementation was administered daily for 60 days, following which nutrition intake, productivity, and growth performance were assessed. Results revealed a dose-dependent increase in nutrition intake with higher levels of bamboo leaf supplementation, indicating improved feed consumption in supplemented groups. Productivity, measured as total weight gain per hectare, exhibited a similar trend, with the Medium and High Dose groups demonstrating higher productivity compared to the Control and Low Dose groups. Analysis of growth performance, represented by average daily gain (ADG), further supported these findings, showing higher ADG in the Medium and High Dose groups. Bamboo leaf supplementation positively influenced nutrition intake, productivity, and growth performance in Boer goats. These results suggest the potential of bamboo leaves as a valuable dietary supplement for enhancing goat farming efficiency and livelihoods, particularly in regions where bamboo is abundant.